2020
DOI: 10.1002/pbc.28373
|View full text |Cite
|
Sign up to set email alerts
|

Development of second primary tumors and outcomes in medulloblastoma by treatment modality: A Surveillance, Epidemiology, and End Results analysis

Abstract: Background As treatment modalities for medulloblastoma have developed and overall survival (OS) has improved, there are relatively limited data on the impact of long‐term effects such as risk of second primary tumors (SPT). To address the knowledge gap, we analyzed factors associated with the risk of SPT and OS by treatment modality for medulloblastoma. Methods We queried the Surveillance, Epidemiology, and End Results (SEER)‐18 database for patients diagnosed with medulloblastoma in 1973‐2014. Patients were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 34 publications
2
10
0
Order By: Relevance
“…Reassuringly, there was no treatment-related mortality during the concurrent phase in our study, although three toxic deaths were documented during adjuvant chemotherapy. Development of second new primary and late noncancer mortality (excluding toxic deaths) that appear seemingly high in our study was quite similar to that reported from the Childhood Cancer Survivor Study (CCSS) 30 and Surveillance Epidemiology and End Results (SEER) analysis 31 with mature and long-term follow-up. In conclusion, our understanding, definition, and management of high-risk/metastatic medulloblastoma have evolved considerably over the last four decades resulting in progressive and consistent improvement in survival.…”
Section: Discussionsupporting
confidence: 88%
“…Reassuringly, there was no treatment-related mortality during the concurrent phase in our study, although three toxic deaths were documented during adjuvant chemotherapy. Development of second new primary and late noncancer mortality (excluding toxic deaths) that appear seemingly high in our study was quite similar to that reported from the Childhood Cancer Survivor Study (CCSS) 30 and Surveillance Epidemiology and End Results (SEER) analysis 31 with mature and long-term follow-up. In conclusion, our understanding, definition, and management of high-risk/metastatic medulloblastoma have evolved considerably over the last four decades resulting in progressive and consistent improvement in survival.…”
Section: Discussionsupporting
confidence: 88%
“…Therefore, the youngest age group may have been exposed to less RT than the other groups. Similarly, data from SEER 18 showed that patients in the 11‐ to 20‐year‐old group had the highest percentage of SPTs in comparison with other age groups 12 …”
Section: Discussionmentioning
confidence: 90%
“…In the Childhood Cancer Survivor Study, the cumulative incidence at 30 years of SPTs among 381 medulloblastoma survivors, treated in 1970‐1985, was 7.8% 13 . Next, the percentage risk from other SEER data for patients diagnosed from 1973 to 2014 were SPT incidence rates of 3.1% and 4.9% at 10 and 15 years, respectively 12 . Another population‐based study of patients with medulloblastoma from the United States and Sweden showed a 5.5‐fold excess incidence of SMNs 14 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations